Hepatoprotective effect of the solvent extracts of Viola canescens Wall. ex. Roxb. against CCl4 induced toxicity through antioxidant and membrane stabilizing activity. Issue 1 (December 2017) - Abdullah,; Khan, Mir; Ahmad, Waqar; Ahmad, Manzoor; Nisar, Mohammad
Abstract Background Viola canescens Wall. ex. Roxb. exhibits analgesic, antimalarial and antispasmodic activities. It is used folklorically for the treatment of liver diseases, hypertension, malaria and cancer. The current study investigates phytochemical constituents, antioxidant and hepatoprotective activity of solvent extracts of whole plant ofViola canescens. Methods Phytochemicals, acute toxicity study and antioxidant activity ofViola canescens methanolic extract (VCME), ethyl acetate fraction (EAF), and partially purified EAF (90% EAF and combination of 80% EAF + 20% methanol fraction (EAF + Me) was carried out. Hepatoprotective activity of VCME, EAF (200 and 400 mg/kg body weight) and partially purified EAF (50 mg/kg body weight) was investigated in carbon tetrachloride (CCl4 ) intoxicated BALB/c mice for 7 days. Membrane stabilization effect was determined by hypotonic solution induced hemolysis while DNA ladder assay was carried out by polyacrylamide gel electrophoresis. Results Phytochemical screening of VCME showed the presence of alkaloids, phenols, flavonoids, saponins, carbohydrates, tannins and triterpenes. VCME, EAF (at 200 and 400 mg/kg body weight) and partially purified EAF (90% EAF and EAF + Me) at 50 mg/kg body weight significantly reduced the level of ALT, ALP, total bilirubin and restored the level of serum protein in comparison to CCl4 treated group. A significant reduction in malondialdehyde (MDA) and elevation in catalase (CAT) and superoxide dismutase (SOD) level was observed in extract treated animals as compared to CCl4 (p  < 0.05). The IC50 values in membrane stabilization potential for VCME, EAF and sodium salicylate were 3.7 ± 0.11, 3.4 ± 0.15 and 3.2 ± 0.09 mg/ml, respectively. Similarly, CCl4 induced degradation of DNA was counteracted by VCME and EAF. The liver biopsy of mice treated with the solvent extracts showed remarkable restoration of normal histological archeitecture. Conclusions Viola canescens showed significant hepatoprotective potential due to its antioxidant and membrane stabilization effect.